Algerian university libraries websites: evaluation study - Fatheddine Bahi (Social Empowerment Journal, 2022)
The field of libraries and information is one of those many fields that have been affected by the Internet, which obliged university libraries to keep pace with developments and establish websites for them on the Internet.Our study, tagged with the title of Algerian university libraries websites: an evaluation study, aims to evaluate the Algerian university libraries websites, in order to reveal the strengths and weaknesses in them, in order to change the traditional style of the library and make proposals to improve and activate these websites to provide high quality services.So that we shed light on university libraries and their services and then the websites of libraries and their most prominent services, we also touched on the evaluation component as it is our evaluation study, and then we included criteria that contain indicators for evaluating the websites of libraries and the bodies responsible for issuing them, so that we touched on analyzing the websites of libraries according to these criteria, The results of the study concluded that most of the sites of Algerian university libraries are weak and do not provide complete and quality services such as: lack of modernization, lack of ongoing briefing and selective broadcasting.